Self-assessment of eligibility for early medical abortion using m-Health to calculate gestational age in Cape Town, South Africa: a feasibility pilot study. Issue 1 (December 2016) - Momberg, Mariette; Harries, Jane; Constant, Deborah
Abstract Background Although abortion is legally available in South Africa, barriers to access exist. Early medical abortion is available to women with a gestational age up to 63 days and timely access is essential. This study aimed to determine women's acceptability and ability to self-assess eligibility for early medical abortion using an online gestational age calculator. Women's acceptability, views and preferences of using mobile technology for gestational age (GA) determination were explored. No previous studies to ascertain the accuracy of online self-administered calculators in a non-clinical setting have been conducted. Methods A convenience sample of abortion seekers were recruited from two health care clinics in Cape Town, South Africa in 2014. Seventy-eight women were enrolled and tasked with completing an online self-assessment by entering the first day of their last menstrual period (LMP) onto a website which calculated their GA. A short survey explored the feasibility and acceptability of employing m-Health technology in abortion services. Self-calculated GA was compared with ultrasound gestational age obtained from clinical records. Results Participant mean age was 28 (SD 6.8), 41 % (32/78) had completed high school and 73 % (57/78) reported owning a smart/feature phone. Internet searches for abortion information prior to clinic visit were undertaken by 19/78 (24 %) women. Most participants found the online GA calculator easy to use (91 %; 71/78); thought the calculation was accurate (86 %; 67/78) and that it would be helpful when considering an abortion (94 %; 73/78). Eighty-three percent (65/78) reported regular periods and recalled their LMP (71 %; 55/78). On average women overestimated GA by 0.5 days (SD 14.5) and first sought an abortion 10 days (SD 14.3) after pregnancy confirmation. Conclusions Timely access to information is an essential component of effective abortion services. Advances in the availability of mobile technology represent an opportunity to provide accurate and safe abortion information and services. Our findings indicate that an online GA calculator would be accurate and helpful. GA could be calculated based on LMP recall within an error of 0.5 days, which is not considered clinically significant. An online GA calculator could potentially act as an enabler for women to access safe abortion services sooner.